Customer Journey di Era Omnichannel: Transformasi Perilaku Konsumen dan Implikasi Strategi Digital Marketing - Askarno Askarno; Ade Bani Riyan (Winter Journal: IMWI Student Research Journal, 2026)
The rapid development of the digital ecosystem has driven a fundamental shift in the way consumers interact with brands. Customer journeys that were originally linear have now transformed into complex, non-linear, and involve multiple digital and physical touchpoints simultaneously. This article aims to critically analyze the transformation of the customer journey in the omnichannel era, identify the accompanying changes in consumer behavior, and formulate strategic implications for digital marketers. Using the Systematic Literature Review (SLR) approach sourced from Google Scholar, Scopus, Web of Science, and SINTA databases with the publication period of 2015–2024, a total of 38 relevant articles were selected through a PRISMA framework-based inclusion-exclusion process. The results of the literature synthesis show that omnichannel integration effectively improves the consistency of the customer experience, strengthens brand loyalty, and creates data-driven personalization opportunities that have not been optimally utilized by most companies. It was also found that the use of artificial intelligence (AI), machine learning, and real-time data analytics are the differentiating factors in the successful implementation of omnichannel strategies. This article contributes to the development of an Omnichannel Journey Integration Framework (OJIF) conceptual framework that integrates four strategic layers and can be the foundation of advanced empirical research.